The open cluster Havlen-Moffat No. 1 revisited - Vázquez, Rubén Ángel (2001)
A deep CCD UBVRI photometric survey combined with UBVRI polarimetric observations of 21 bright stars was carried out in the region of the open cluster Havlen-Moffat No. 1. Our data reveal that the extinction law in this cluster is variable and that six cluster stars show very high polarisation values (>4%), probably because of the presence of a nearby small dust cloud. The cluster is at a distance of d = 3300 pc, it is 2-4 Myr old and the initial mass function of its most massive stars (M > 3 M⊙) has a flat slope of x ≈ 0.7. As an additional result, it was possible to reconcile the absolute magnitudes of the two WN7-type members using the R-values valid in the regions where they are located.